Mathematical communication of 7th-grade students viewed from the attitude of curiosity in Guided Discovery Learning assisted by educational props - Sabani, Mas'ud; Isnarto, Isnarto (Unnes Journal of Mathematics Education, 2020)
The purpose of this study is (1) to find out the mastery learning achievement of students mathematical communication ability in Guided Discovery learning assisted by educational props, (2) know the improvement of mathematical communication ability in Guided Discovery learning supported by educational props (3) describe students mathematical communication ability for each category curiosity in Guided Discovery learning assisted by educational props. This research method is mixed methods with sequential explanatory design. The population in this study were all students of class VII SMP N 33 Semarang in 2019/2020; sampling was done by random sampling selected to be a sample is class VII-F. The research subjects were taken by using a purposive sampling technique. The research subjects consisted of 9 students. Subjects were interviewed based on mathematical communication ability test results. The results showed that (1) students mathematical communication ability in Guided Discovery learning assisted by educational props reached mastery learning, with an average grade reaching 80 and classical completeness exceeding 75%, (2) there was an increase in students' mathematical communication ability in Guided Discovery learning assisted by educational props. Improved mathematical communication ability is medium. (3) Subjects with high curiosity have four indicators of mathematical communication ability; subjects with curiosity have three indicators of mathematical communication ability; subjects with low curiosity only have two indicators of mathematical communication ability.